Plant species as indicators of geochemical anomalies: Experiences onIlex aquifolium (holly) (Environmental Geology, 1995)
The distribution of Zn, Cd, Pb, and Cu, in plants growing in mineralized and sterile areas of Tuscany has been studied to verify if and to what extent metal- accumulating species represent evidence of geochemical anomalies in soils. Samples of leaves and twigs from trees were collected, and analyzed by means of differential pulse anodic stripping voltammetry (DPASV). Hollies, bram- bles, and Holm oaks in particular were considered in the mineralized area of Bottino, and the special aptitude of hollies in concentrating Cd with respect to the other metals has been verified. Cadmium has been previously recog- nized as a pathfinder for zinc ore bodies; the results of this investigation appear to point out the relevance of holly as a bioindicator of geochemical zinc anomalies. Lower metal concentration characterizes the same species from other mineralized and sterile zones, with the exception of the urbanized area of Florence, where relatively higher Zn concentrations in hollies appear to be due to atmospheric pollution.